Review Pengaruh Metode Adsorpsi sebagai Pre-Treatment dan Metode Pemurnian Kering dalam Pembuatan Biodiesel Menggunakan Minyak Jelantah - Risty, Amelia Eka; Rohmawati, Rizqi; Alfiani, Masita; Suwarno, Kukuh Hadi; Nurkaswoto, Setiya Eko; Awaludin, Aditya Fikri (Institut Teknologi Adhi Tama Surabaya, 2025)
Biodiesel is an alternative fuel used in diesel engines. Biodiesel can be produced from various types of biomass that exist in nature. Biodiesel processing is the process of converting from triglycerides into fatty acid methyl esters (FAME). The biodiesel production method develops with a variety of processes selected based on the conditions of the raw material and the quality of biodiesel to be achieved. Biodiesel production can use conventional methods such as esterification with acid catalysts and transesterification with base catalysts. Despite there are also new methods such as subcritical and supercritical processes in the absence of a catalyst. The general method of purifying biodiesel is the wet washing and dry washing process, a conventional method for removing biodiesel impurities such as soap, catalysts, glycerol, and alcohol residues using water as a washing agent. Acids can also be used as washing agents, such as phosphoric acid, sulfuric acid, and hydrochloric acid. Dry-washing is a purification method using an ion exchange resin. The biodiesel refining process can also be done using membranes. Besides, there are also ionic liquids and eutectic solvents formed from a mixture of organic halide salts and organic compounds that can be applied in the purification of biodiesel.